Beyond Orientalist Binaries: Domestic Praxis and Muslim Womanhood in Contemporary South Asian Fiction - Azim, Md Samiul; Hoque, Md Akidul; Parvin, Farida (UIN Syarif Hidayatullah Jakarta, 2025)
This study interrogates the persistence of binary representations of Muslim women within Orientalist discourse. It examines how contemporary South Asian English fiction, authored by writers from the Indian subcontinent, actively subverts these reductive paradigms. Drawing on postcolonial feminist theory and Islamic feminist studies, the research employs a comparative qualitative analysis of selected novels: Kamila Shamsie’s Home Fire, Tahmima Anam’s A Golden Age, and Nazia Erum’s Mothering a Muslim. Close readings of character development, narrative voice, and symbolic motifs reveal that these works reconceptualize Muslim womanhood through articulations of agency, resilience, and intellectual autonomy. Key findings demonstrate that the veil emerges as both a marker of cultural identity and a site of resistance; that wartime and postcolonial traumas are reconfigured to foreground female subjectivity; and that other narrative strategies operate as critical tools for challenging patriarchal norms. The study concludes that such literary interventions dismantle Orientalist binaries—East/West, secular/religious, traditional/modern—and offer nuanced articulations of faith-inflected feminist praxis. By bridging postcolonial and Islamic feminist frameworks, this research advances the field of Muslimah literature and contributes to broader debates on representation, agency, and intersectionality in global Anglophone fiction.